2010
DOI: 10.1016/j.bbadis.2010.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Signaling mechanisms that link salt retention to hypertension: Endogenous ouabain, the Na+ pump, the Na+/Ca2+ exchanger and TRPC proteins

Abstract: Salt retention as a result of chronic, excessive dietary salt intake, is widely accepted as one of the most common causes of hypertension. In a small minority of cases, enhanced Na+ reabsorption by the kidney can be traced to specific genetic defects of salt transport, or pathological conditions of the kidney, adrenal cortex, or pituitary. Far more frequently, however, the salt retention may be the result of minor renal injury or small genetic variation in renal salt transport mechanisms. How the salt retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
63
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 192 publications
2
63
0
Order By: Relevance
“…Whereas a 1 represents the housekeeping enzyme expressed by all cells, most cell types additionally express NaKA with another a isoform: astrocytes, endothelial cells, and VSMCs express a 2 whereas most neurons express a 3 . 25 Interestingly, Hajek and colleagues reported that prolonged increase of [K þ ] o significantly reduced NaKA activity in astrocytic culture. Therefore, we investigated whether NaKA activity is reduced by increase of [K þ ] ACSF to a level that was previously found to induce SI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas a 1 represents the housekeeping enzyme expressed by all cells, most cell types additionally express NaKA with another a isoform: astrocytes, endothelial cells, and VSMCs express a 2 whereas most neurons express a 3 . 25 Interestingly, Hajek and colleagues reported that prolonged increase of [K þ ] o significantly reduced NaKA activity in astrocytic culture. Therefore, we investigated whether NaKA activity is reduced by increase of [K þ ] ACSF to a level that was previously found to induce SI.…”
Section: Discussionmentioning
confidence: 99%
“…87 Another limitation is that the concept of intracellular Ca 2þ regulation by high affinity NaKAs has been partially based on other vascular beds than the cerebral circulation. 25,56 More research is thus needed to investigate these mechanisms in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed major differences in the physiological functions of each isoform. For example, the ␣2 isoform appears to possess the unique ability to regulate intracellular Ca 2ϩ levels in myocytes and coresides with the Na ϩ /Ca 2ϩ exchanger (5,24). In addition, recent experiments using SWAP mice (ouabainsensitive ␣1 Na-K-ATPase mutant and ouabain-resistant ␣2 Na-K-ATPase mutant) suggest that the ␣2 isoform plays a more prominent role in calcium release in cardiac and smooth muscle myocytes than ␣1 (12).…”
mentioning
confidence: 99%
“…Effects of acute ANG II infusions on urine flow and U Na V. Before acute ANG II infusions, there were no significant differences in urine flow ( (1,3,5). The latter are composed, at least in part, of C-type transient receptor potential (TRPC) channel proteins (3,5).…”
mentioning
confidence: 99%
“…The latter are composed, at least in part, of C-type transient receptor potential (TRPC) channel proteins (3,5). Additionally, NCX plays a role in smooth muscle Ca homeostasis; in particular, NCX-mediated Ca 2ϩ entry is important for the maintenance of vascular tone (1,3,5).…”
mentioning
confidence: 99%